2006
DOI: 10.1016/j.quageo.2006.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Limited ice-sheet erosion and complex exposure histories derived from in situ cosmogenic 10Be, 26Al, and 14C on Baffin Island, Arctic Canada

Abstract: Discordant cosmogenic nuclide exposure ages derived from 10 Be, 26 Al, and 14 C extracted from quartz in rocky summits along the eastern rim of the central Baffin Island plateau provide constraints on the efficiency of erosion by the Laurentide Ice Sheet (LIS) and on the timing and duration of ice-free conditions in the eastern Canadian Arctic. In situ 14 C records the duration of exposure during the present interglaciation; any previously acquired 14 C decayed below detection limits beneath thick LIS duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 49 publications
6
55
0
Order By: Relevance
“…However, the surfaces likely have experienced some form of glacial disturbance (e.g., rotated blocks in a basal shear zone; Atkins et al, 2002) during the last glacial cycle because some samples have concentrations significantly lower than highly weathered tor-like forms on uplands along the outer fjords . Miller et al (2006) report companion 26 Al data for the two samples reported here with the highest 10 Be concentration (CR04-10 and CR04-12); these 26 Al concentrations, when combined with the 10 Be concentrations, require N 450 kyr of surface history. On the Be concentrations were measured at Lawrence Livermore National Laboratory and scaled to site-specific altitude using Stone (2000).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the surfaces likely have experienced some form of glacial disturbance (e.g., rotated blocks in a basal shear zone; Atkins et al, 2002) during the last glacial cycle because some samples have concentrations significantly lower than highly weathered tor-like forms on uplands along the outer fjords . Miller et al (2006) report companion 26 Al data for the two samples reported here with the highest 10 Be concentration (CR04-10 and CR04-12); these 26 Al concentrations, when combined with the 10 Be concentrations, require N 450 kyr of surface history. On the Be concentrations were measured at Lawrence Livermore National Laboratory and scaled to site-specific altitude using Stone (2000).…”
Section: Discussionmentioning
confidence: 75%
“…The apparent 10 Be ages of the erratics also pre-date deglaciation of the summit (∼13 ka based on in-situ 14 C exposure ages from summit bedrock; Miller et al, 2006), and thus either were deposited during the last glaciation with inheritance or were emplaced during an earlier glacial episode and subsequently overrun. Either explanation is equally plausible.…”
Section: Discussionmentioning
confidence: 97%
“…For quantifying shorter burial events, a promising nuclide is in-situ produced 14 C, which has a half-life of only 5,700 years, and which therefore decays rapidly enough to be significantly altered when covered by ice for just a few thousand years. Miller et al (2006) and Briner et al (2014) Cosmogenic exposure dating is rapidly evolving with refinements in both measurement and calculation techniques (Balco, 2011). An important improvement in measurement accuracy 31 was achieved for the most commonly used nuclide, 10 Be, when Nishiizumi et al (2007) accurately determined Be ratios of several different standards used to measure 10 Be concentrations.…”
Section: Cosmogenic Datingmentioning
confidence: 99%
“…Although 10 Be inheritance is common in polar landscapes Davis et al, 1999, Marsella et al, 2000Briner et al, 2006;Miller et al, 2006;Corbett et al, 2013Corbett et al, , 2016Margreth et al, 2016), our study is one of the first to suggest that non-erosive, cold-based ice sheets are a factor to be considered in temperate mountainous regions. As suggested in Bierman et al (2015), variable glacial erosion rates between summits and valleys may play a strong role in development and maintenance of northern Appalachian topography through the Quaternary.…”
Section: Discussionmentioning
confidence: 57%